THE EFFECT OF THINK PAIR SHARE TEACHING STRATEGY TO STUDENTSâ SELF-CONFIDENCE AND SPEAKING COMPETENCY OF THE SECOND GRADE STUDENTS OF SMPN 6 SINGARAJA - I M. Permadi, Utama,; Marhaeni, A.A.I.N; Adi Jaya, I Nyoman (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract The aim of this study was to investigate the effect of think pair share teaching strategy to studentsâ self-confidence and studentsâ speaking competency. This study was conducted towards students of the second grade in SMPN 6 Singaraja, in the academic year 2012/2013. There were 121 students selected as sample put in experimental and control group. The study used a post-test only control group design. The analysis was made by using Manova facilitated by SPSS version 16.0 for windows. The result indicated that (1) there was a significance effect of Think Pair Share on studentsâ self-confidence (F = 754.104 and sig = 0.000; p < 0.05). (2) there was a significance effect of Think Pair Share on studentsâ speaking competency (F = 60.325 and sig = 0.000; p < 0.05). (3) simultaneously, there was significance effect of Think Pair Share on studentsâ self-confidence and studentsâ speaking competency (<0.05).